Is there an optimal number of oocytes retrieved at which live birth rates or cumulative live birth rates per aspiration are maximized after ART? A systematic review. Issue 1 (January 2021) - Law, Yin Jun; Zhang, Ning; Kolibianakis, Efstratios M.; Costello, Michael F.; Keller, Elena; Chambers, Georgina M.; Venetis, Christos A.
Abstract: The association between the number of oocytes retrieved and fresh live birth rate (LBR) or cumulative LBR (CLBR), and whether an optimal number of oocytes are retrieved when LBR or CLBR are maximized, are highly relevant clinical questions; however published results are conflicting. A systematic review of all eligible studies ( n  = 16) published until January 2020 on MEDLINE, Embase, Scopus, CINAHL and Web of Science was conducted. Five studies evaluated only LBR from fresh cycles, five studies evaluated only CLBR from stimulated cycles and six evaluated both. A marked difference was observed between the oocyte yields at which LBR and CLBR were reportedly maximized in the individual studies. On the basis of nine studies, the optimal number of oocytes at which fresh LBR seems to be maximized is proposed to be between 12 and 18 oocytes (15 oocytes was the most common suggestion). On the other hand, CLBR continues to increase with the number of oocytes retrieved. This is the first systematic review on the topic, and it suggests that the retrieval of 12–18 oocytes is associated with maximal fresh LBR, whereas a continuing positive association is present between the number of oocytes retrieved and CLBR.